2020
DOI: 10.1634/theoncologist.2019-0894
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Vitamin B12 Levels Associated with C-Reactive Protein in Older Patients with Cancer

Abstract: Background. A Comprehensive Geriatric Assessment (CGA) has been proposed to assess prognosis and to adapt oncological care in older patients with cancer. However, few biological markers are incorporated in the CGA. Methods. This comparative study on older patients with cancer was realized before final therapeutic decision and during a CGA that included biological markers. Our objective study was to know if the serum vitamin B12-C-reactive protein index (BCI) can help to estimate early death and unplanned hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the present study, this association remained signifcant after adjustment for cancer, BMI, albumin level, and ICU referral, suggesting B12 is an independent marker of poor prognosis. High B12 levels have been suggested as part of a frailty score in association with cancer, liver disease, or cardiovascular disease [36][37][38]. Indeed, if elevated B12 is independently associated with mortality, combining this with other poor prognostic factors such as low albumin or chronic disease is likely to improve its impact.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, this association remained signifcant after adjustment for cancer, BMI, albumin level, and ICU referral, suggesting B12 is an independent marker of poor prognosis. High B12 levels have been suggested as part of a frailty score in association with cancer, liver disease, or cardiovascular disease [36][37][38]. Indeed, if elevated B12 is independently associated with mortality, combining this with other poor prognostic factors such as low albumin or chronic disease is likely to improve its impact.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Couderc et al (2020) studied the effects of hypercobalaminemia in 621 older cancer adults in outpatient care with a median age of 81 years. Their study demonstrated that hypercobalaminemia and vitamin B12-C-reactive protein index may constitute important markers for older cancer frail patients with poor prognosis[ 34 ].…”
Section: Investigating the B12-frailty Interplaymentioning
confidence: 99%
“…Moreover, vitamin B12 has also been postulated as a useful biomarker of severity (prognosis) and death in such diseases [5][6][7], as well as, increased vitamin B12 concentrations might paradoxically be masking a deficiency [8]. This functional deficiency is associated with alterations in the uptake and tissue processing of cobalamin, or with the presence of antibodymediated analytical interferences such as macrocomplexes of vitamin B12 [macroB12, generally with immunoglobulins (immunocomplexes)] [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%